Woolfolk And Moran’s Psychometric Properties Of Teachers’ Sense Of Efficacy Scale In The Algerian Environment - Chenine Fateh Eddine; Khouildat Samira (University of Eloued جامعة الوادي, 2024)
Abstract: The current study aims to measure the psychometric characteristics of the Teacher's Sense of Efficacy measure of Woolfolk and Tschannen-Moran (2001) on the Algerian environment in its lengthy Arabic version; Using the descriptive curriculum and applying it to a sample of primary education professors of 195 They work in Algerian schools in the city of Ouargla, which have been selected in the form of random cluster surveys; Honesty calculated Discriminatory for items and sincerity of internal consistency, half-split stability as well as internal consistency stability through calculation Cronbach's alpha; The results of this have resulted in the scale enjoying good honesty indicators, and high reliability indicators, from which we have concluded The measure of Teachers' Sense of Efficacy, as expressed in the Algerian environment, has psychometric characteristics consistent with Good scale specifications
Keywords: Teachers' Sense of Efficacy; professor of primary education; psychometric characteristics; honesty; reliability